Analisis Pembiayaan Mudharabah Terhadap Peningkatan Laba Bersih Pada PT. Bank Perkreditan Rakyat Syariah Amanah Insan Cita William Iskandar Medan - Muslih Muslih (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2017)
This study aims to determine (1) how mudharabah financing in PT. BPR Syariah Amanah Insan Cita, (2) to find out why mudharabah financing decreases in 2015, (3) to know the ability of mudharabah financing in generating profit at PT. BPR Syariah Amanah Insan Cita William Iskandar Medan. The method used in this research is descriptive analysis with case study approach. The technique of collecting data is done through primary data that is data obtained directly from the data source where this research conducted at PT. BPR Syariah Amanah Insan Cita William Iskandar Medan and secondary data are data obtained from the literature and books that have to do with the problem to be studied. The analysis tool used is trend analysis. The results showed that the ability of mudharabah financing in generating profits can be said to be able to increase profits for the company although the financing decreased the profit generated increased. mudharabah financing has a significant ability to increase net income for the company.